P089 The cost of repeat ANA testing in north west London pathology services. (26th April 2021) - Colquhoun, Matthew; Mouyis, Maria
Abstract: Background/Aims The anti-nuclear antibody (ANA) test is commonly used to screen for autoimmune connective tissue (CTD) disease. It is a test that should be used judiciously and should only be requested if a patient presents with symptoms suggestive of a CTD and should not be used as a screening test for vague musculoskeletal symptoms. Recent studies have demonstrated that it is often repetitively requested in those patients both with a known positive and known negative ANA with little value in altering a diagnosis. With this information in mind, we sought to examine the frequency and associated cost of repeat ANA testing in hospital trusts served by North West London Pathology Services (NWL). Methods The trusts included in the study were Imperial College Healthcare NHS Trust, Chelsea and Westminster Hospital Foundation Trust and Hillingdon Hospitals NHS Foundation Trust. Data was obtained regarding how many patients had repeat ANA testing in total between these trusts between 2017-2019. The data was obtained via a freedom of information request. Results In total, there were 6, 799 instances of repeated ANA testing in the same patient across three trusts over three years. This included one patient who had 16 ANA tests in a single year in 2017. The cost of an ANA test is £12.27. The total cost of repeat ANA testing in the three years across three trusts was £83, 423.73 (£27, 807.66 per year on average). Data is provided in tabular form and gives a breakdown of the number of repeat ANA tests per year and how many times the test was repeated in the same patient. Conclusion The requesting of unnecessary tests can add to a hospital pathology workload and is associated with significant cost. It has been previously demonstrated in the literature that repeat ANA testing is of little value and rarely alters the diagnosis of a rheumatic disease. There is a large burden of repeated ANA testing in North West London Pathology Services and this is associated with significant expense. More judicious use of ANA testing can result in significant cost saving. This is the first study to specifically examine the cost of repeat ANA testing in the NHS. Disclosure M. Colquhoun: Other; MC has received support to attend conferences from Pfizer. M. Mouyis: None.